Two-stage kinetic analysis of fragrance evaporation and absorption from skin - Saiyasombati, P.; Kasting, G. B. (International journal of cosmetic science, 2003)
Synopsis Human in vivo fragrance evaporation data from a previously published study are reanalysed in terms of compartmental pharmacokinetic models in which the microscopic rate constants are functions of the physicochemical properties of the fragrance components. According to the proposed analysis, which is restricted to low doses, absorption and evaporation of each component are first‐order processes occurring from either the skin (one‐compartment model) or the skin and a more rapidly depleted vehicle layer (two‐compartment models). Evaporation rates of ingredients from a 12‐component mixture containing a musk fixative followed single exponential decays that were well described by the one‐compartment model. An otherwise identical mixture without fixative yielded evaporation rates that could be characterized as biexponential decays associated with loss from two compartments. This result shows that ingredient interactions qualitatively and quantitatively change evaporation rate profiles of fragrance components; however, an attempt to account for these interactions explicitly by means of activity coefficients inserted as multipliers for the microscopic rate constants was unsuccessful. Re‐examination of this approach in the context of a diffusion/evaporation model is suggested. The developed models have potential utility for dermal risk assessment and for prediction of aroma evolution following topical application of complex fragrances. Résumé Des données d'une étude publiée précédemment sur l'évaporation de parfum de humaine in vivo sont réanalysées en utilisant des modèles pharmacocinétiques compartimentés dont les constants microscopiques de taux sont des functions des propriétés physio‐chimiques des composants de parfum. Selon l'analyse proposée, qui est limitée aux petites doses, l'absorption et l'évaporation de chaque composant sont des processus de premier ordre se produisant l'un de la peau (modèle d'un compartiment), ou l'autre de la peau et d'une couche de véhicule plus rapidement épuisée (modèles de deux compartiments). Les taux d'évaporation d'ingrédients d'un mélange de 12 composants contenant un fixatif de musc suivi par des décompositions exponentielles uniques qui ont été bien décrites par le modèle d'un compartiment. Un mélange sans fixatif mais identique pour le reste a rapporté des taux d'évaporation qui pourraient être caractérisés commes des décompositions bi‐exponentielles avec une perte de deux compartiments. Ce résultat montre que les interactions d'ingrédient changent qualitativement et quantitativement les profils de taux d'évaporation des composants de parfum. Cependant, une tentative d'expliquer précisement ces interactions au moyen des coefficients d'activité insérés comme multiplicateurs pour les constants microscopiques de taux n'a pas été réussie. Le réexamen de cette approche dans le contexte d'un modèle de diffusion/evaporation est suggéré. Les modèles développés ont une utilité potentielle dans l'évaluation des risques cutané et pour la prévision de l'évolution d'arome suivant l'application topique des parfums complexes.